Real-world data from the Portuguese Nivolumab Expanded Access Program (EAP) in previously treated Non Small Cell Lung Cancer (NSCLC) - Figueiredo, A. (2020)
Objective: The main aim of the study was to evaluate the efficacy and safety profile of Nivolumab, an immune-checkpoint-inhibitor antibody, in advanced, previously treated, Non-Small Cell Lung Cancer (NSCLC) patients, in a real world setting. Methods: We performed a retrospective, multicentre data analysis of patients who were included in the Portuguese Nivolumab Expanded Access Program (EAP). Eligibility criteria included histologically or citologically confirmed NSCLC, stage IIIB and IV, evaluable disease, sufficient organ function and at least one prior line of chemotherapy. The endpoints included Overall Response Rate (ORR), Disease Control Rate (DCR), Progression Free Survival (PFS) and Overall Survival (OS). Safety analysis was performed with the National Cancer Institute Common Terminology Criteria for Adverse Events (CTCAE), version 4.0, and immune-related Adverse Events (irAEs) were treated according to protocol treatment guidelines. Tumour response was assessed using the Response Evaluation Criteria in Solid Tumours (RECIST) version 1.1. Data was analysed using SPSS, version 21.0 (IBM Statistics). Results: From June 2015 to December 2016, a total of 229 patients with advanced NSCLC were enrolled at 30 Portuguese centres. Clinical data were collected up to the end of July 2018. The baseline median age was 64 years (range 37-83) and the majority of patients were males (70.3%) and former/current smokers (69.4%). Patients with non-squamous histology predominated (88.1%), and 67.6% of the patients had received 2 or more prior lines of chemotherapy. Out of 229 patients, data was available for 219 patients (3 patients did not start treatment, while data was unavailable in 7 patients); of the 219 patients, 15.5% were not evaluated for radiological tumour assessment, 1.4% had complete response (CR), 21% partial response (PR), 31% stable disease (SD) and 31.1% progressive disease (PD). Thus, the ORR was 22.4% and DCR was 53.4% in this population. At the time of survival analysis the median PFS was 4.91 months (95% CI, 3.89-6.11) and median OS was 13.21 months (95% CI, 9.89-16.53). The safety profile was in line with clinical trial data. Conclusions: Efficacy and safety results observed in this retrospective analysis were consistent with observations reported in clinical trials and from other centres.